A study of vibration exposure and work practices of Loader and Dozer operators in opencast mines - Bibhuti Bhusan Mandal; Krishnendu Sarkar; Veena Manwar (Occupational Health and Safety Society of Nepal, 2012)
Exposure to whole body vibration (WBV) at work and development of musculoskeletal disorders are well linked. Vehicle vibrations are usually perceived to occur in vertical direction and are likely to cause lumbar disorders in operators. Vibration characteristics of the machines need to be studied and compared with work practices which may indicate nature of health risk to operators. This may help in developing specific action plans to control vibration related health risk. The objectives of the study were, to measure and analyze vibration magnitudes, observe work practices of Loaders and Dozers, evaluate health risk to their operators and to formulate recommendations for control measures. Frequency weighted Root Mean Square values of acceleration data was collected as per guidelines in ISO 2631 -1:1997 using human vibration analyzers. WBV exposure of 40 (Forty) Loader and Dozer operators in eight opencast mines were evaluated to assess health risk using vibration magnitude and corresponding daily exposure durations. The dominant axis of vibration in dozers was found to be X (front to back) in 80% of the equipment. This is different from transporting equipment like Dumpers which have Z axis as dominant axis of vibration. A continuous change of movement in forward and reverse direction and rash driving were found to be contributory factors for increased vibration intensity along X- axis. It was observed that 27(68%) of them showed moderate whereas 12(30%) equipment showed high health risk. It is suggested that vibration control measures should be designed and adopted based not only on the intensity but also on the dominant axis typical to the equipment and work practices.